2020
DOI: 10.1016/j.ecoenv.2019.110103
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous cleanup of Reactive Black 5 and cadmium by a desert soil bacterium

Abstract: Multi-contaminated industrial wastewaters pose serious environmental risks due to high toxicity and non-biodegradability. The work reported here evaluated the ability of Pseudomonas aeruginosa strain Gb30 isolated from desert soil to simultaneously remove cadmium (Cd) and Reactive Black 5 (RB5), both common contaminants in various industrial effluents. The strain was able to grow normally and decolorize 50 mg L -1 RB5 within 24 h of incubation in the presence of 0.629 m mol L -1 of Cd 2+ . In order to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Among these microorganisms, bacteria have strong potential for the treatment of TIWWPs because these are easy to culture with fast life phase and capable to grow on different substances [57]. Further, bacteria can degrade or convert many toxic compounds into non-toxic products [5].…”
Section: Biological Treatment Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these microorganisms, bacteria have strong potential for the treatment of TIWWPs because these are easy to culture with fast life phase and capable to grow on different substances [57]. Further, bacteria can degrade or convert many toxic compounds into non-toxic products [5].…”
Section: Biological Treatment Approachesmentioning
confidence: 99%
“…Further, bacteria can degrade or convert many toxic compounds into non-toxic products [5]. For example, many bacterial species like Arthrobacter, Pseudomonas, Bacillus, Aeromonas hydrophila and Lysinibacillus are reported capable to remove dyes, dissolved solids and heavy metals as well as reduce their toxicity upto a significant level [5,15,57]. Further, for the effective treatment of TIWW, various workers have reported that microbial consortium is more effective as compared to the axenic cultures (Table 3).…”
Section: Biological Treatment Approachesmentioning
confidence: 99%
“…Azo dyes account for the largest category (60-70%) of the total synthetic dyes industry due to their versatility, cost-effectiveness, simplicity of utilization, high stability and high intensity of the color [26,27]. This dye has a prominent chromophore (-N = N-) structure, ensuring the solubility of the dyes in water and its attachment to the fiber [28,29]. Azo dyes are classified into three groups (mono, di and poly) depending on the number of azo groups in their structure (Figure 1).…”
Section: Azo Dyesmentioning
confidence: 99%
“…When the total monomer concentration is low, the probability of contact and collision between the monomers is low, so that the substitution and addition reactions cannot proceed ultimately, and the molecular chain of the generated organic high molecular polymer is short. The generation amount is small [26]. On the other hand, the total monomer concentration increases.…”
Section: Effect Of Photoinitiator Concentration On Mf@aa Flocculation Performancementioning
confidence: 93%